Understanding the uterine artery Doppler waveform and its relationship to spiral artery remodelling - Lloyd-Davies, C; Collins, SL; Burton, GJ (Elsevier, 2021)
Analysis of the uterine artery (UtA) Doppler waveform is frequently used in high-risk pregnancies to assess the likelihood of adverse pregnancy outcomes, including preeclampsia and fetal growth restriction. Whilst abnormal UtA waveforms at 18-20 weeks are associated with adverse outcomes, the underlying cause of these waveform changes remains unknown. Current evidence suggests the long-held dogma that the UtA waveform is merely a reflection of trophoblast-induced spiral artery remodelling is incorrect. Hence, the origins of the waveform changes must be reassessed. Recent data from human and animal models suggests that the arcuate arteries, placental bed arterio-venous anastomoses and, most notably, the radial arteries may be more important in determining the UtA waveform profile than previously appreciated. Furthermore, there is increasing evidence implicating the maternal cardiovascular system in the pathophysiology of the complications predicted by the waveform changes, particularly preeclampsia, and therefore its underlying association with the UtA waveform warrants further investigation.